Posterior oblique ligament of the knee: state of the art. Issue 5 (May 2021) - D'Ambrosi, Riccardo; Corona, Katia; Guerra, Germano; Cerciello, Simone; Ursino, Chiara; Ursino, Nicola; Hantes, Michael
Abstract : The posterior oblique ligament (POL) is the predominant ligamentous structure on the posterior medial corner of the knee joint. A thorough understanding of the anatomy, biomechanics, diagnosis, treatment and rehabilitation of POL injuries will aid orthopaedic surgeons in the management of these injuries. The resulting rotational instability, in addition to valgus laxity, may not be tolerated by athletes participating in pivoting sports. The most common mechanism of injury – accounting for 72% of cases – is related to sports activity, particularly football, basketball and skiing. Moreover, three different injury patterns have been reported: those associated with injury to the capsular arm of the semimembranosus (SM), those involving a complete peripheral meniscal detachment and those involving disruption of the SM and peripheral meniscal detachment. The hallmark of an injury related to POL lesions is the presence of anteromedial rotatory instability (AMRI), which is defined as 'external rotation with anterior subluxation of the medial tibial plateau relative to the distal femur'. In acute settings, POL lesions can be easily identified using coronal and axial magnetic resonance imaging (MRI) where the medial collateral ligament (MCL) and POL appear as separate structures. However, MRI is not sensitive in chronic cases. Surgical treatment of the medial side leads to satisfactory clinical results in a multi-ligamentous reconstruction scenario, but it is known to be associated with secondary stiffness. In young patients with high functional demands, return to sports is allowed no earlier than 9–12 months after they have undergone a thorough rehabilitation programme. Cite this article: EFORT Open Rev 2021;6:364-371. DOI: 10.1302/2058-5241.6.200127